Integrated treatment approaches in sports physiotherapy for individuals with obesity (Research, Society and Development, 2024)
Introduction: Obesity is a global public health problem, related to an increased risk of chronic diseases and reduced quality of life. Sports physiotherapy, within a multidisciplinary approach, can act to prevent injuries and promote health in obese individuals. Objective: To evaluate the contribution of sports physiotherapy to the management of obesity, focusing on preventing injuries and improving functional and mobility aspects. Methodology: The research adopted a narrative review, with searches in scientific databases to identify studies that analyzed physiotherapeutic interventions, including strength training, manual therapy, myofascial release, and proprioceptive exercises. Results: The findings suggest that physiotherapeutic interventions, when combined with physical exercise programs, contribute to significant improvements in the functional capacity, mobility, body composition, and quality of life of obese individuals. Conclusion: Sports physiotherapy demonstrates potential to assist in the management of obesity and promote the health of these individuals. However, additional research is needed to define clear guidelines and more effective practices in physical therapy aimed at this population.